System of Leukocytes Respiratory Burst Activity (RBA) in Grouper (Epinephelus coioides) - Anggraini Ratih Purwandari; Dwi Nur Rikhma Sari (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
Probiotics are live microbes that can help protect and maintain the health of the host by modifying the microbial community or associating with the host, increasing the response to disease, improving nutrition, and utilizing feed. Probiotics have properties to increase feed efficiency and increase non-specific immunity in fish. Probiotic administration allows fish to achieve optimal growth and increase immunity to disease. Therefore, in this study used probiotics containing bacteria Bacillus subtilis. The purpose of this study was to determine the effect of probiotic Bacillus subtilis endoprore administration on the respiratory burst activity (RBA) immune system in grouper (Epinephelus coioides). The results of the research showed that the administration of probiotics in the grouper (Epinehelus coioides) feed with the probiotic dose of Bacillus subtilis in Feed B (0.1% Bacillus subtilis) and Feed C (1 % Bacillus subtilis) had a significantly effect on Respiratory Burst Activity (RBA) compared to Feed A (0% Bacillus subtilis). In addition, the administration of probiotic Bacillus subtilis in the grouper feed was also able to increase the total number of bacteria in the rearing media, whereas an increasing in the number of bacteria in the B and C feed treatments indicated a better rearing media for the growth of grouper. The RBA values ​​in Feed B (0.1% Bacillus subtilis) and Feed C (1 % Bacillus subtilis) were significantly different start from 10 days of rearing time. While the best dose for the RBA value is Feed C with an elapsed time 30 days.